Monocyte-Derived Dendritic Cells Are Essential for CD8+ T Cell Activation and Antitumor Responses After Local Immunotherapy - Kuhn, Sabine; Yang, Jianping; Ronchese, Franca (Frontiers in Immunology, 2015)
Tumors harbor several populations of dendritic cells with the ability to prime tumor-specific T cells. However, these T cells mostly fail to differentiate into armed effectors and are unable to control tumor growth. We have previously shown that treatment with immunostimulatory agents at the tumor site can activate anti-tumor immune responses, and is associated with the appearance of a population of monocyte-derived dendritic cells in the tumor and tumor-draining lymph node. Here we use dendritic cell or monocyte depletion and monocyte transfer to show that these monocyte-derived dendritic cells are critical to the activation of anti-tumor immune responses. Treatment with the immunostimulatory agents Monosodium Urate crystals and Mycobacterium smegmatis induced the accumulation of monocytes in the draining lymph node, their upregulation of CD11c and MHCII, and expression of iNOS, TNFα and IL12p40. Blocking monocyte entry into the lymph node and tumor through neutralization of the chemokine CCL2 or inhibition of Colony Stimulating Factor-1 receptor signaling prevented the generation of monocyte-derived dendritic cells, the infiltration of tumor-specific T cells into the tumor, and anti-tumor responses. In a reciprocal fashion, monocytes transferred into mice depleted of CD11c+ cells were sufficient to rescue CD8+ T cell priming in lymph node and delay tumor growth. Thus monocytes exposed to the appropriate conditions become powerful activators of tumor-specific CD8+ T cells and anti-tumor immunity.